Mineralogy And Geochemical Study Of Air Piau, Kelantan Gold Prospect (Drill Core) - Abdul Nashir, Mohd Khairul Nidzam (Universiti Sains Malaysia, 2018)
The average concentration of gold in the Earth’s crust is mostly about 0.005 g/t, which is much lower than the other metallic metals. Therefore, systematic borehole logging has been conducted on borehole sample. Total depth of borehole is 100 m, so each sample are taken every 25 m which will get four samples to be analysed. Besides that, the samples were being chosen based on the characteristic and appearance that they showed along the depth. The objectives are to identify the geology and potential gold mineralization in the prospect including observing the grade of the gold and other metallic element by knowing their concentration. In this research, minerals such as pyrite, quartz and arsenopyrite are the major mineral in the gold particle such identified from the SEMEDX analysis. Other than that, quartz was the highest result that can be known based on the peak pattern analysed by XRD, followed with mineral pyrite and rutile. Major oxide element that can be obtained from samples were Fe2O3,SiO2 and TiO2, that had been analysed by XRF. For chemical analysis in this research, gold in sample B (depth at 52.2m) at Air Piau showed the highest concentration than other samples which had been analysed by AAS analysis. As a conclusion, the best method to analyse gold was by using ICP-OES because the detection limit was better than AAS analysis. This was suitable for analysing exploration sample which not promising any high value.